Unintended pregnancy and abortion by income, region, and the legal status of abortion: estimates from a comprehensive model for 1990–2019 - Bearak, Jonathan; Popinchalk, Anna; Ganatra, Bela; Moller, Ann-Beth; Tunçalp, Özge; Beavin, Cynthia; Kwok, Lorraine; Alkema, Leontine (The Lancet global health, 2020)
Unintended pregnancy and abortion estimates document trends in sexual and reproductive health and autonomy. These estimates inform and motivate investment in global health programmes and policies. Variability in the availability and reliability of data poses challenges for measuring and monitoring trends in unintended pregnancy and abortion. We developed a new statistical model that jointly estimated unintended pregnancy and abortion that aimed to better inform efforts towards global equity in sexual and reproductive health and rights. We developed a model that simultaneously estimated incidence of unintended pregnancy and abortion within a Bayesian framework. Data on pregnancy intentions and abortion were compiled from country-based surveys, official statistics, and published studies found through a literature search, and we obtained data on livebirths from the World Population Prospects. We analysed results by World Bank income groups, Sustainable Development Goal regional groupings, and the legal status of abortion. In 2015–19, there were 121·0 million unintended pregnancies annually (80% uncertainty interval [UI] 112·8–131·5), corresponding to a global rate of 64 unintended pregnancies (UI 60–70) per 1000 women aged 15–49 years. 61% (58–63) of unintended pregnancies ended in abortion (totalling 73·3 million abortions annually [66·7–82·0]), corresponding to a global abortion rate of 39 abortions (36–44) per 1000 women aged 15–49 years. Using World Bank income groups, we found an inverse relationship between unintended pregnancy and income, whereas abortion rates varied non-monotonically across groups. In countries where abortion was restricted, the proportion of unintended pregnancies ending in abortion had increased compared with the proportion for 1990–94, and the unintended pregnancy rates were higher than in countries where abortion was broadly legal. Between 1990–94 and 2015–19, the global unintended pregnancy rate has declined, whereas the proportion of unintended pregnancies ending in abortion has increased. As a result, the global average abortion rate in 2015–19 was roughly equal to the estimates for 1990–94. Our findings suggest that people in high-income countries have better access to sexual and reproductive health care than those in low-income countries. Our findings indicate that individuals seek abortion even in settings where it is restricted. These findings emphasise the importance of ensuring access to the full spectrum of sexual and reproductive health services, including contraception and abortion care, and for additional investment towards equity in health-care services. UK Aid from the UK Government, Dutch Ministry of Foreign Affairs, UNDP/UNFPA/UNICEF/WHO/World Bank Special Programme of Research, Development and Research Training in Human Reproduction (HRP), and The Bill & Melinda Gates Foundation.